Distributed energy resource system optimisation using mixed integer linear programming - Omu, Akomeno; Choudhary, Ruchi; Boies, Adam (Energy policy, 2013)
In this study a mixed integer linear programming (MILP) model is created for the design (i.e. technology selection, unit sizing, unit location, and distribution network structure) of a distributed energy system that meets the electricity and heating demands of a cluster of commercial and residential buildings while minimising annual investment and operating cost. The model is used to analyse the economic and environmental impacts of distributed energy systems at the neighbourhood scale in comparison to conventional centralised energy generation systems. Additionally, the influence of energy subsidies, such as the UK's Renewable Heat Incentives and Feed in Tariffs, is analysed to determine if they have the desired effect of increasing the economic competitiveness of renewable energy systems. •A MILP model was created to design a distributed energy resource system for a cluster of buildings.•The optimal DER system was found to decrease annual costs by 40% and CO2 emissions by 50%.•Small wind turbines and biomass boilers were found to be the optimal technologies.•Energy subsidies are vital because they increase the affordability of low carbon technologies.